2001
DOI: 10.1063/1.1381547
|View full text |Cite
|
Sign up to set email alerts
|

Two-color amorphous silicon image sensor

Abstract: Soft lithographic fabrication of an image sensor array on a curved substrateA large-area two-color image sensor array made with amorphous silicon ͑a-Si:H͒ technology is described. Mesa-isolated double-junction p-i-n-i-p a-Si:H sensors discriminate the two spectral bands-blue/green and red-according to the polarity of the applied voltage bias. The 512ϫ512 element active-matrix array with 75 m pixel pitch is addressed using a-Si:H thin-film switching transistors. Under steady state illumination, the array exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A recent study of color sensors found exactly this effect and a detailed analysis of the relation between the series resistance and the image lag is given. 15 Furthermore, other measurements have shown the nonuniform internal field that indicates the presence of a depletion layer in the PbI 2 layers. Time-of-flight transport studies of simple films found that the response is different if the measurement is performed promptly or a longer time after the voltage is applied.…”
Section: Depletion Layer Model For Pbi 2 Charge Collectionmentioning
confidence: 99%
“…A recent study of color sensors found exactly this effect and a detailed analysis of the relation between the series resistance and the image lag is given. 15 Furthermore, other measurements have shown the nonuniform internal field that indicates the presence of a depletion layer in the PbI 2 layers. Time-of-flight transport studies of simple films found that the response is different if the measurement is performed promptly or a longer time after the voltage is applied.…”
Section: Depletion Layer Model For Pbi 2 Charge Collectionmentioning
confidence: 99%
“…The sensor exhibited peak responses at 520 and 650 nm, with "reasonably good" color separation but with excellent response linearity as a function of the incident light intensity, while the resolution of the images captured with this array exceeded 300 dpi [121,122].…”
Section: Thin Film Color Sensorsmentioning
confidence: 97%
“…The use of multilayered structures based on a-SiC:H alloys as color sensors has been an important topic of research in the field of sensing applications [1,2,3]. In these multilayered devices the light filtering is achieved through the use of different band gap materials, namely a-Si 1-x C x :H. In these devices the spectral sensitivity in the visible range is controlled by the external applied voltage.…”
Section: Introductionmentioning
confidence: 99%